2004
DOI: 10.1111/j.0001-5172.2004.00460.x
|View full text |Cite
|
Sign up to set email alerts
|

Hyperoxic ventilation at the critical hematocrit: Effects on myocardial perfusion and function

Abstract: Hyperoxic ventilation at Hctcrit is followed by coronary vasoconstriction and reduction of coronary blood flow. However, myocardial oxygenation and function is maintained, as increased O2-content (in particular dissolved O2) preserves myocardial oxygenation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 42 publications
1
14
0
1
Order By: Relevance
“…We did not examine a response curve to graded level of hemodilution because targeting hematocrit values Ͻ25% was associated with unstable hemodynamic condition following surgical preparation. The occurrence of cardiac failure has been documented during graded hemodilution at hematocrit values Ͻ10% in healthy anesthetized animals (49) and around 20 -22% in those with a critical coronary stenosis (18, 40 -42). The importance of hemodynamic stability during acute coronary occlusion should be emphasized since any decrease in blood pressure, even within the normal range, has been shown to worsen myocardial damage (29).…”
Section: Discussionmentioning
confidence: 99%
“…We did not examine a response curve to graded level of hemodilution because targeting hematocrit values Ͻ25% was associated with unstable hemodynamic condition following surgical preparation. The occurrence of cardiac failure has been documented during graded hemodilution at hematocrit values Ͻ10% in healthy anesthetized animals (49) and around 20 -22% in those with a critical coronary stenosis (18, 40 -42). The importance of hemodynamic stability during acute coronary occlusion should be emphasized since any decrease in blood pressure, even within the normal range, has been shown to worsen myocardial damage (29).…”
Section: Discussionmentioning
confidence: 99%
“…A high F i O 2 may lead to vasoconstriction in tissue beds, e.g. coronary vasoconstriction [24] . Hyperoxia may cause maldistribution of blood flow and deterioration of blood flow at the level of the distribution vessels as a protective mechanism against high p O 2 , leading to decreased oxygen uptake in spite of unchanged O 2 delivery [25] .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, an increase in Hb concentration from 6.0 to 7.8 g/dl with RBC transfusion is capable of reverting hemodilution-induced dysfunctions (24). Other studies have shown that tolerance to moderate hemodilution can be effectively managed with hyperoxic ventilation, which improves tissue oxygenation and survival (15,19). These beneficial effects have been attributed to an increase in arterial O 2 content via an increase of physically dissolved O 2 in the plasma, an increase in MAP, and coronary perfusion pressure, due to hyperoxic arteriolar vasoconstriction.…”
Section: Discussionmentioning
confidence: 99%